A Boarder, a Widow, and a Tenant Sit Down for Dinner: Foodway Comparisons in the Goose Hill Neighborhood, East St. Louis, Illinois. Issue 1 (2nd January 2017) - Dappert-Coonrod, Claire P.; Kuehn, Steven R.
ABSTRACT: During the turn of the twentieth century, the Goose Hill neighborhood in East St. Louis, Illinois, was predominantly a working-class population largely employed at the National Stockyards and its related industries. Many people in Goose Hill lived in multifamily homes or rentals, though a few did own homes. In this study, foodways comparisons between inhabitants of a boardinghouse, a long-term stable household, and a high-turnover tenancy highlight differences and similarities between such divergent types of households. It also illustrates and provides a discussion of priorities and consumer preferences within each household. This case study presents one viable way in which such a methodological framework can be used to approach interpretation of turn-of-the-twentieth-century urban archaeological sites and assemblages. It also highlights the strengths and shortcomings of such a multi-evidentiary approach.